2005
DOI: 10.1038/sj.onc.1208642
|View full text |Cite
|
Sign up to set email alerts
|

Loss of BNIP3 expression is a late event in pancreatic cancer contributing to chemoresistance and worsened prognosis

Abstract: Altered expression of apoptosis-regulating genes plays an important role in the aggressive growth behavior and chemoresistance of pancreatic ductal adenocarcinoma. In the present study, the hypoxia-inducible proapoptotic gene, BNIP3, was analysed in terms of expression, effect on patient survival, and chemo-responsiveness in pancreatic cancer cell lines. cDNA microarray, real-time light cycler s quantitative polymerase chain reaction, laser-capture microdissection, and immunohistochemistry analyses were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
158
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(166 citation statements)
references
References 59 publications
6
158
0
1
Order By: Relevance
“…In our study, there was low efficiency of Runx2 silencing, although the current protocol used for siRNA transfection has been used for other genes (Berberat et al, 2005;Erkan et al, 2005;Kayed et al, 2005). Furthermore, two additional Runx2 siRNA sequences were used, and these exhibited even lower silencing efficiencies than the one that was used in the final experiments.…”
Section: Discussionmentioning
confidence: 89%
“…In our study, there was low efficiency of Runx2 silencing, although the current protocol used for siRNA transfection has been used for other genes (Berberat et al, 2005;Erkan et al, 2005;Kayed et al, 2005). Furthermore, two additional Runx2 siRNA sequences were used, and these exhibited even lower silencing efficiencies than the one that was used in the final experiments.…”
Section: Discussionmentioning
confidence: 89%
“…The amount of nuclear versus cytoplasmic BNIP3 expression in different tumor types is shown in Table 2 and discussed below. Nuclear BNIP3 is detected in GBM tumors, 57 nonsmall cell lung tumors, 62 cervical tumors, 59 breast tumors 61 and prostate tumors, 56 and a perinuclear BNIP3 staining pattern is observed in pancreatic tumors 72 and colorectal adenocarcinomas. 69 In prostate tumors, there is a correlation between cytoplasmic BNIP3 expression and Gleason score, age AR and GLUT1 expression, but nuclear BNIP3 did not correlate with any clinicopathological factors.…”
Section: Bnip3mentioning
confidence: 99%
“…The more aggressive subclass A HCC showed a higher level of bnip3 promoter methylation than the less aggressive B type. 72 bnip3 gene was found to be methylated in multiple myeloma (MM) patient samples and was significantly correlated with poor patient survival rates. Trichostatin A (HDAC inhibitor) and Aza-dC treatment of MM cell lines lead to an increase in the expression of BNIP3.…”
Section: Bnip3mentioning
confidence: 99%
See 1 more Smart Citation
“…Erkan et al and Akada et al showed that silencing of BNIP3 by small interfering RNA (siRNA) correlated with increased chemoresistance. 29,30 Mahon et al showed that the knockdown of S100A4, a repressor of the BNIP3 promoter-mediated reporter gene expression, resulted in an elevated expression of BNIP3 and the activation of apoptotic mediators in PC cell lines, resulting in an increased sensitivity to gemcitabine treatment. 12 The treatment by Wack et al with adenoviral systems for proapoptotic Bax and TNF-related apoptosis-inducing ligand (TRAIL) expression targeting, using the human telomerase reverse transcriptase (hTERT) promoter, resulted in high-level expression of Bax and TRAIL, genes directly related to apoptosis induction in gemcitabine-resistant cell lines with a significant tumor regression and prolongation of in vivo survival.…”
Section: Apoptosismentioning
confidence: 99%